“Evaluación de tres distancias de siembra del cultivo de Jengibre (Zingiber officinale) con aplicaciones foliar y edáfico de tierra de diatomeas" - Palacios Cedeño, Jennifer Beatriz (2022)
This research was carried out in Chipe Hamburgo 2 in El Triunfo parish of La Maná canton to evaluate the agronomic response of three planting distances of the ginger crop with foliar and edaphic applications of diatomaceous earth. For which, the following objectives are considered: To identify the effects of different planting distances of the ginger crop with the diatomaceous earth application. To determine the method of diatomaceous earth application for better production results and economically, and to analyze the treatments to know the optimal results in terms of economic benefits. A completely randomized block design was applied, with seven treatments corresponding to the interaction between planting distances and diatomaceous earth application methods, plus a control. The variables evaluated were: vegetative development variables: days to plant emergence, percentage of emergence, and plant height; production variables: number of tillers, length and weight of rhizomes, yield per hectare, and cost analysis. As a result, the lowest days to emergence were obtained 19 days after planting with T3 (40 cm/plant - foliar application), and the highest percentage of emergence was obtained with T4 (40 cm/plant with edaphic application) with 94.00% of plants emerged. The best results in plant height were obtained with T1 (20 cm/plant with foliar application) with 31.57 cm in 30 days, and after 60 days of evaluation T3 (40 cm/plant with foliar application) obtained the higher plant height with 62.31 cm and at 90 days with the same treatment with 83.98 cm in height. As for the number of tillers, T4 (40 cm/plant with soil application) showed higher results with 20.50 tillers per plant. The number of rhizomes was higher in T4 (40 cm/plant with edaphic application) with 10.63 rhizomes on average, while the higher length of rhizomes was in T4 (40 cm/plant with edaphic application) with 24.50 cm. The heaviest rhizomes were obtained with T4 (40 cm/plant with edaphic application) with 259.43g, giving an efficiency of 13.21 ton/ha. The economic analysis determined that the applications of diatomaceous earth at planting distances of 60 cm, with two application methods, presented high production costs USD. 9.31 per treatment, while T4 (40 cm/plant with edaphic application) obtained the highest income with USD. 15.38 and a benefit/cost ratio of USD. 0.74 for each dollar invested in ginger production.